Climate Change and Urban Heat Islands in India: A Review Across Nine Urban Agglomerations - Nidhi Sinha (International Journal of Climate Conditions, 2026)
Since 1901, anthropogenic climate change has raised India's mean surface temperatures by about 0.9°C, compounding warming. Rapid urbanization creates persistent Urban Heat Islands (UHIs), making cities dangerously hotter than rural areas. A combination of these forces presents acute thermal hazards to hundreds of millions of urban dwellers. The paper discusses the emergence and intensification of UHI in nine large Indian cities (Delhi-NCR, Ahmedabad, Chennai, Hyderabad, Kolkata, Pune, Bengaluru, Mumbai, and Patna) between 2001 and 2024. Based on MODIS-based data on the Intensity of Surface Urban Heat Island at night (SUHII) and land-use change, and IMD meteorological data, the study reports steady decadal increases in SUHII in all cities. The value of Ahmedabad was the highest absolute (3.1 °C); Bengaluru had the highest relative change (67 percent). The expansion of the built-up area and a decrease in the vegetation cover become the central factors in each city under consideration. The understudied yet acutely susceptible node in the Indo-Gangetic Plain, Patna, is given special consideration. The paper concludes with policy measures that include greening the urban areas, protection of water bodies, the implementation of cool roofs, and also the expansion of the heat action plans to the secondary cities. Furthermore, the study highlights that increasing heat stress in urban environments can adversely affect public health, energy demand, labor productivity, and overall quality of life. Vulnerable populations, including the elderly, children, and low-income communities, are disproportionately affected by prolonged exposure to elevated temperatures. Strengthening climate-resilient urban planning, integrating sustainable infrastructure, and adopting nature-based solutions are essential strategies to mitigate future urban heat risks and enhance adaptive capacity across rapidly growing Indian cities.
Keywords: Climate change; Heat Stress; Patna; Urban heat island (UHI); land use land cover change; multi-city India; surface UHI intensity (SUHII); urban greening